High-wear-resistance anhydrous phosphogypsum-based self-leveling thermal insulation mortar and preparation method thereof
By adding modified glass fiber and composite wear-resistant materials to the gypsum-based self-leveling mortar, combined with the modification of semi-hydrophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophorophor The problem of low chemical activity achieves high wear resistance and high thermal insulation properties.
Patent Information
- Application Number
- CN202411688060.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
The wear resistance of existing gypsum-based self-leveling mortars is insufficient, resulting in short life and low hydration activity of anhydrous phosphogypsum, resulting in low resource utilization.
The formula of high wear-resistant anhydrous phosphogypsum-based self-leveling insulation mortar, including anhydrous phosphogypsum, semi-hydrous phosphogypsum, modified glass fiber, composite wear-resistant materials, etc., is adopted to add modified glass fiber and composite wear-resistant materials. , improve the wear resistance of the mortar, and improve the hydration activity of anhydrous phosphogypsum through the combination of semi-hydrophosphogypsum and calcium chloride.
It significantly improves the wear resistance and insulation properties of the mortar, extends the service life, and realizes the efficient utilization of anhydrous phosphogypsum resources.
Smart Images

Figure BDA0005150148130000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a phosphogypsum-based self-leveling thermal insulation mortar and a preparation method thereof. Background Art
[0002] Gypsum-based self-leveling mortar is a new type of environmentally friendly mortar different from cement-based self-leveling mortar. It has the characteristics of early strength and fast hardening, precise leveling, not easy to crack, not easy to hollow, high construction efficiency, etc. After hardening, it feels warm and comfortable underfoot and can be breathable and humidified.
[0003] At present, high-strength gypsum or building gypsum is generally used to prepare gypsum-based self-leveling mortar, and it has been promoted and applied in many places in recent years. Anhydrous gypsum, which is also in large stock, is rarely used because anhydrous phosphogypsum has low hydration activity and slow coagulation and hardening. The existing method to increase its activity is mainly to calcine it to semi-hydrated phosphogypsum before application, but this method will significantly increase energy consumption.
[0004] Gypsum-based self-leveling mortar still has obvious defects, the most important of which is its poor wear resistance and short life. When gypsum-based self-leveling mortar is used as a floor material, its surface is directly subjected to ground wear. The thickness of the self-leveling mortar is relatively thin during construction. When the ground base is solid, the force it bears is mainly concentrated on the surface. The surface damage of many floor materials is due to insufficient surface wear resistance. Soon after being used, it shows peeling, sanding, and pockmarking. It can be said that wear resistance is one of the important indicators of the durability of gypsum self-leveling mortar.
[0005] Existing research mainly selects high-strength gypsum and reinforced aggregate to improve wear resistance. CN 113372079 A uses desulfurized gypsum, sulfoaluminum cement, steel slag, etc. to prepare high-wear-resistant gypsum-based self-leveling mortar; CN 106316318 A uses fluorinated gypsum and hard aggregate to enhance wear resistance; CN 108046727 A uses mixed metal and carbon fiber to enhance wear resistance. However, the above-mentioned method of improving wear resistance by only selecting high-strength gypsum and reinforcing aggregate cannot, on the one hand, solve the problem of resource utilization of anhydrous gypsum, and on the other hand, cannot play the role of maximizing wear resistance. Therefore, researching and developing a highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar and finding a method for preparing the mortar are practical problems that need to be solved urgently. Summary of the invention
[0006] In view of the problems of low utilization rate and insufficient wear resistance of anhydrous phosphogypsum in the prior art, the present invention provides a highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar and a preparation method thereof, which overcomes the problems of low hydration activity and slow coagulation and hardening of anhydrous phosphogypsum and the influence of impurities faced by hemihydrate gypsum, realizes the resource utilization of anhydrous phosphogypsum in the field of self-leveling thermal insulation mortar, and has excellent wear resistance and thermal insulation properties.
[0007] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0008] A highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar, the composition of which is calculated by weight as follows:
[0009] 70-80 parts of anhydrous phosphogypsum, 5-10 parts of hemihydrate phosphogypsum, 4-6 parts of thermal insulation filler, 0.5-1.5 parts of modified glass fiber, 2-4 parts of composite wear-resistant material, 1-2 parts of redispersible latex powder, 0.1-0.3 parts of sodium polyacrylate, 8-12 parts of river sand, 0.5-0.7 parts of calcium chloride, 0.2-0.4 parts of water reducer, 0.05-0.15 parts of retarder, and 30-40 parts of water.
[0010] In the above scheme, the anhydrous phosphogypsum is obtained by calcining type II anhydrous phosphogypsum at 750° C. for 2 hours, grinding it to a particle size of less than 5 μm and a pH value of 5-6.
[0011] In the above scheme, the hemihydrate phosphogypsum is β-type building phosphogypsum, with a pH value of 6-8 and a whiteness of ≥80%.
[0012] In the above scheme, the thermal insulation filler is prepared by mixing discarded foam glass and rock wool powder in a mass ratio of 1:1, wherein the average particle size of the foam glass is 0.2-0.4 mm, and the average particle size of the rock wool powder is 5-6 μm.
[0013] In the above scheme, the preparation method of the modified glass fiber comprises the following steps:
[0014] The glass fiber is immersed in a mixed system containing a coupling agent, a water-based epoxy resin and a curing agent, and after immersion for 20-40 minutes, it is taken out and dispersed, and placed at 30-50°C to accelerate curing; by weight, the water-based epoxy resin is 2.5-5 parts, the curing agent is 0.5-1 part, and the coupling agent is 0.3-0.4 parts;
[0015] The glass fiber has a length of 0.2-0.4 mm, a diameter of 0.01-0.02 mm, and a density of 2.4-2.6 g / cm 3 ;
[0016] The water-based epoxy resin is one of DW-100 and DW-200 produced by Shandong Dongfang Hongye Chemical;
[0017] The curing agent is one of ethylenediamine, triethylamine and diethylenetriamine;
[0018] The coupling agent is a zirconate coupling agent.
[0019] In the above scheme, the composite wear-resistant material is a mixture of aluminum oxide, zirconium oxide and shell particles in a mass ratio of 1:1:2; the particle size is 1-1.5 mm.
[0020] In the above scheme, the solid content of the redispersible latex powder is ≥98%, and the bulk density is 350-450g / L.
[0021] In the above scheme, the sodium polyacrylate is a white powder with a density of 1.2-1.4 g / cm 3 .
[0022] In the above scheme, the particle size of the river sand is ≤0.6mm.
[0023] In the above scheme, the calcium chloride is a white powder with a density of 2.1-2.3 g / cm 3 .
[0024] In the above scheme, the retarder is degraded polyamide calcium salt.
[0025] In the above scheme, the water reducing agent is a polycarboxylic acid high-performance water reducing agent with a water reduction rate of 28-30%.
[0026] The preparation method of the above-mentioned highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar comprises the following steps:
[0027] (1) mixing anhydrous phosphogypsum with hemihydrate phosphogypsum, sodium polyacrylate, calcium chloride, a water reducer, a retarder, and one third of water to obtain slurry 1;
[0028] (2) adding the modified glass fiber and one third of water into slurry 1, mixing, stirring and dispersing the mixture to obtain slurry 2;
[0029] (3) Add river sand, composite wear-resistant material, thermal insulation filler, redispersible latex powder and one-third of water into slurry 2, stir at high speed to disperse evenly, and obtain highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention grinds anhydrous phosphogypsum powder into fine powder, and uses a small amount of hemihydrate phosphogypsum in combination with calcium chloride to modify the powder to improve its activity, and then further accelerates the hydration process under the thickening and water retention effects of sodium polyacrylate, thereby reducing the setting time and achieving the same hydration effect as phosphate building gypsum. At the same time, the problem of impurity influence faced by hemihydrate gypsum can be solved, and anhydrous phosphogypsum has advantages and a broad market in realizing the resource utilization of industrial by-product gypsum.
[0032] (2) The present invention not only improves the bonding force between the fiber and the matrix by adding glass fiber modified by zirconate coupling agent and water-based epoxy resin to the anhydrous phosphogypsum-based self-leveling mortar, but also the coupling agent hydrolyzed groups attached to the surface of the modified glass fiber can form a stable calcium silicate hydrate with the calcium ions in the phosphogypsum, providing a more stable crystallization center under the action of the redispersible latex powder, and promoting the formation of anhydrous phosphogypsum hydration products. Finally, high-quality wear-resistant river sand and composite wear-resistant materials are used to greatly enhance the wear resistance of the slurry.
[0033] (3) The present invention adopts discarded foam glass and rock wool powder as thermal insulation fillers, which improves the thermal insulation performance while reducing the cost compared with conventionally used vitrified microspheres. The anhydrous phosphogypsum-based self-leveling thermal insulation mortar of the present invention has excellent wear resistance and thermal insulation performance and can be used as an indoor floor surface layer. DETAILED DESCRIPTION
[0034] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0035] A specific embodiment provides a method for preparing modified glass fiber:
[0036] Clean the glass fiber and remove dust and grease on the surface; mix the coupling agent with an appropriate amount of water-based epoxy resin and curing agent evenly and stir at high speed for 5-10 minutes; soak the cleaned glass fiber for 30 minutes, take it out and disperse it, and accelerate the curing at 40°C; after curing, cool the modified glass fiber to room temperature. 5 types of modified glass fibers are specifically provided, as shown in Table 1. The water-based epoxy resin specifically uses DW-100 from Shandong Oriental Hongye Chemical, and the curing agent uses a matching amine curing agent. The glass fiber has a length of 0.2-0.4mm, a diameter of 0.01-0.02mm, and a density of 2.4-2.6g / cm 3 .
[0037] Table 1
[0038] raw material Modified glass fiber 1 Modified glass fiber 2 Modified glass fiber 3 Modified glass fiber 4 Modified glass fiber 5 Fiberglass 0.5 serving 0.75 serving 1 serving 1.25 servings 1.5 servings Waterborne Epoxy Resin 2.5 servings 3 servings 4 servings 4.5 servings 5 servings Curing agent 0.5 serving 0.6 parts 0.8 parts 0.9 parts 1 serving Coupling agent 0.3 parts 0.32 copies 0.34 0.36 copies 0.4 parts
[0039] The specific implementation method also provides a method for preparing a highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar:
[0040] 1) grinding anhydrous phosphogypsum to less than 5 μm by a ball mill, dividing water into three parts, and then mixing the ground anhydrous phosphogypsum with hemihydrate phosphogypsum, sodium polyacrylate, calcium chloride, a water reducer, a retarder, and one part of water to obtain slurry 1;
[0041] 2) adding the modified glass fiber and one portion of water into slurry 1 to obtain slurry 2;
[0042] 4) Add high-quality river sand, composite wear-resistant materials, thermal insulation fillers, redispersible latex powder, and one portion of water to slurry 2, stir at high speed for 3-5 minutes, and then pour the fully stirred slurry into a triple mold;
[0043] 5) Curing the fiber under the conditions of 20±2°C, 70%-80% humidity and 28 days, and then drying the fiber to constant weight to test its wear resistance and thermal insulation performance. The raw material ratios are shown in Table 2, wherein Examples 1-5 respectively use modified glass fibers 1-5.
[0044] Table 2
[0045] raw material Example 1 Example 2 Example 3 Example 4 Example 5 Anhydrous phosphogypsum 60 servings 62 servings 65 servings 68 servings 70 servings Hemihydrate phosphogypsum 5 servings 6 servings 8 servings 9 servings 10 servings Insulation filler 4 servings 4.5 servings 5 servings 5.5 servings 6 servings Modified glass fiber 0.5 serving 0.75 serving 1 serving 1.25 servings 1.5 servings Composite wear-resistant materials 2 servings 2.5 servings 3 servings 3.5 servings 4 servings Redispersible latex powder 1 serving 1.25 servings 1.5 servings 1.75 servings 2 servings Sodium polyacrylate 0.1 part 0.15 0.2 parts 0.25 0.3 parts High quality river sand 8 servings 9 servings 10 servings 11 servings 12 servings Calcium chloride 0.5 serving 0.55 serving 0.6 parts 0.65 0.7 parts Water reducing agent 0.2 parts 0.25 0.3 parts 0.35 0.4 parts Retarder 0.05 0.07 0.09 0.11 parts 0.15 water 30 servings 33 servings 35 servings 37 servings 40 servings
[0046] The specific implementation method also supplements comparative experiments, which are as follows:
[0047] Comparative Example 1: The difference between Comparative Example 1 and Example 4 is that no modified glass fiber is added.
[0048] Comparative Example 2: The difference between Comparative Example 2 and Example 4 is that no modified glass fiber is added, and no composite wear-resistant material or high-quality river sand is added.
[0049] Comparative Example 3: The difference between Comparative Example 3 and Example 4 is that the thermal insulation filler is replaced by glass microspheres in equal amounts.
[0050] The performance of the mortar specimens of the above-mentioned embodiments and comparative examples after absolute drying and constant weight was tested. When characterizing the wear resistance, the formed test block was placed on a GLM-200 steel wheel wear tester for testing, and the wear resistance was evaluated by the wear amount index of 1min, 2min, and 3min. Obviously, the smaller the wear amount, the better the wear resistance; when characterizing the thermal insulation performance, the thermal conductivity coefficient was tested with reference to JG / T266-2011 "Foamed Concrete". The smaller the thermal conductivity coefficient, the better the thermal insulation performance. The results are shown in Table 3.
[0051] Table 3
[0052]
[0053]
[0054] As can be seen from Table 3, Example 4 only lost 0.08g after 2min of wear on the GLM-200 steel wheel wear tester, and there was no further loss when it was worn to 3min. In terms of 3min wear, Example 4 lost 0.7g less than Example 1 and 1.17g less than Example 2, indicating that the use of coupling agent to modify glass fiber and combine with water-based epoxy resin can greatly improve the wear resistance of anhydrous phosphogypsum-based self-leveling thermal insulation mortar, and the effect of improving wear resistance is best when combined with other wear-resistant materials. From the test results of thermal conductivity, the use of discarded glass bubbles and rock wool powder is only 4.4% higher than that of vitrified microspheres, and the thermal insulation effect is still good, but at this time it is obviously much lower than the vitrified microspheres. The production cost has a good economic benefit.
[0055] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar, characterized in that The composition is calculated by weight as follows: 70-80 parts of anhydrous phosphogypsum, 5-10 parts of hemihydrate phosphogypsum, 4-6 parts of thermal insulation filler, 0.5-1.5 parts of modified glass fiber, 2-4 parts of composite wear-resistant material, 1-2 parts of redispersible latex powder, 0.1-0.3 parts of sodium polyacrylate, 8-12 parts of river sand, 0.5-0.7 parts of calcium chloride, 0.2-0.4 parts of water reducer, 0.05-0.15 parts of retarder, and 30-40 parts of water.
2. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The anhydrous phosphogypsum is obtained by calcining type II anhydrous phosphogypsum at 750° C. for 2 hours, and is ground to a particle size of less than 5 μm and a pH value of 5-6.
3. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that: The semi-hydrated phosphogypsum is β-type building phosphogypsum with a pH value of 6-8 and a whiteness of ≥80%.
4. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The thermal insulation filler is prepared by mixing discarded foam glass and rock wool powder in a mass ratio of 1:1, wherein the average particle size of the foam glass is 0.2-0.4 mm, and the average particle size of the rock wool powder is 5-6 μm.
5. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The preparation method of the modified glass fiber comprises the following steps: The glass fiber is immersed in a mixed system containing a coupling agent, a water-based epoxy resin and a curing agent, and after immersion for 20-40 minutes, it is taken out and dispersed, and placed at 30-50°C to accelerate curing; by weight, the water-based epoxy resin is 2.5-5 parts, the curing agent is 0.5-1 part, and the coupling agent is 0.3-0.4 parts; The glass fiber has a length of 0.2-0.4 mm, a diameter of 0.01-0.02 mm, and a density of 2.4-2.6 g / cm 3 ; The water-based epoxy resin is one of DW-100 and DW-200 produced by Shandong Dongfang Hongye Chemical; The curing agent is one of ethylenediamine, triethylamine and diethylenetriamine; The coupling agent is a zirconate coupling agent.
6. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The composite wear-resistant material is a mixture of aluminum oxide, zirconium oxide and shell particles in a mass ratio of 1:1:2; the particle size is 1-1.5 mm.
7. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The redispersible latex powder has a solid content of ≥98% and a bulk density of 350-450 g / L; the sodium polyacrylate is a white powder with a density of 1.2-1.4 g / cm 3 .
8. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The river sand particle size is ≤0.6mm; the calcium chloride is white powder with a density of 2.1-2.3g / cm 3 .
9. The highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to claim 1, characterized in that The retarder is degraded polyamide calcium salt; the water reducer is a polycarboxylic acid high-performance water reducer with a water reduction rate of 28-30%.
10. The method for preparing the highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar according to any one of claims 1 to 9, characterized in that The following steps are involved: (1) mixing anhydrous phosphogypsum with hemihydrate phosphogypsum, sodium polyacrylate, calcium chloride, a water reducer, a retarder, and one third of water to obtain slurry 1; (2) adding the modified glass fiber and one third of water into slurry 1, mixing, stirring and dispersing the mixture to obtain slurry 2; (3) Add river sand, composite wear-resistant material, thermal insulation filler, redispersible latex powder and one-third of water into slurry 2, stir at high speed to disperse evenly, and obtain highly wear-resistant anhydrous phosphogypsum-based self-leveling thermal insulation mortar.
Citation Information
Patent Citations
Self-leveling wear-resistant floor and preparation method thereof
CN106316318A
Wear-resistant gypsum board
CN108046727A
High-wear-resistance gypsum-based self-leveling mortar and preparation method thereof
CN113372079A